2018
DOI: 10.1519/jsc.0000000000002468
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foam Rolling on Range of Motion, Peak Torque, Muscle Activation, and the Hamstrings-to-Quadriceps Strength Ratios

Abstract: Madoni, SN, Costa, PB, Coburn, JW, and Galpin, AJ. Effects of foam rolling on range of motion, peak torque, muscle activation, and the hamstrings-to-quadriceps strength ratios. J Strength Cond Res 32(7): 1821-1830, 2018-To examine the effects of foam rolling (FR) on range of motion (ROM), peak torque (PT), hamstrings-to-quadriceps (H:Q) ratios, and muscle activation. Twenty-two recreationally active women (mean age ± SD = 21.55 ± 1.82 years, 161.91 ± 6.58 cm, 61.47 ± 10.54 kg) volunteered for this study. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(108 citation statements)
references
References 27 publications
4
94
0
5
Order By: Relevance
“…This is in agreement with several studies that have reported no effect of self-massage on performance (Abels, 2013;Behara & Jacobson, 2017;Halperin et al, 2014;Healey et al, 2014;Jones et al, 2015;MacDonald et al, 2013;Mikesky et al, 2002). Whilst decreases in peak knee flexor torque was reported following FR of the hamstrings by Madoni et al (2018), impairments were similarly observed in a control group (no intervention) and thus no negative effect was concluded. Plantar flexor performance was evaluated in two of the aforementioned investigations.…”
Section: Individual Responsessupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with several studies that have reported no effect of self-massage on performance (Abels, 2013;Behara & Jacobson, 2017;Halperin et al, 2014;Healey et al, 2014;Jones et al, 2015;MacDonald et al, 2013;Mikesky et al, 2002). Whilst decreases in peak knee flexor torque was reported following FR of the hamstrings by Madoni et al (2018), impairments were similarly observed in a control group (no intervention) and thus no negative effect was concluded. Plantar flexor performance was evaluated in two of the aforementioned investigations.…”
Section: Individual Responsessupporting
confidence: 91%
“…Foam rolling (FR) is a self-massage technique demonstrated to be an effective means for increasing ROM Cheatham, Kolber, Cain, & Lee, 2015). Furthermore, several studies have reported that selfmassage does not negatively influence physical performance (Behara & Jacobson, 2017;Halperin et al, 2014;Healey, Hatfield, Blanpied, Dorfman, & Riebe, 2014;Jones, Brown, Coburn, & Noffal, 2015;MacDonald et al, 2013;Madoni, Costa, Coburn, & Galpin, 2018;Mikesky, Bahamonde, Stanton, Alvey, & Fitton, 2002). Two interventions have sought to determine the influence of self-massage on dorsiflexion ROM.…”
Section: Introductionmentioning
confidence: 99%
“…In shorter times, a few authors also obtained positive results [24,27,65]. In recent studies there is a tendency to roll a few groups of muscles called "regions", one after another [54,69,31,22,35,39]. Also Cheatham et al divided the quadriceps muscle into two zones [8,11].…”
Section: Duration Of Applicationmentioning
confidence: 99%
“…It may be caused by adding up benefits of therapy of a few regions that are lying close to each other. Especially the methodology described by Madoni et al [39] is worth citing. The authors divided hamstring groups into three sections.…”
Section: Duration Of Applicationmentioning
confidence: 99%
See 1 more Smart Citation